New Aspects for the Treatment of Cardiac Diseases Based on the Diversity of Functional Controls on Cardiac Muscles: Mitochondrial Ion Channels and Cardioprotection - Hirofumi Nishida; Toshiaki Sato; Takehiko Ogura; Haruaki Nakaya (Elsevier, 2009)
Mitochondrial ATP-sensitive K+ (mitoKATP) and Ca2+-activated K+ (mitoKCa) channels exist in cardiac myocytes, and they play key roles in cardioprotection. We have recently reported that K+ influx through mitoKATP or mitoKCa channels occurs independently of each other and confers cardioprotection in a similar manner. Activation of mitoKATP channel is augmented by protein kinase C (PKC), whereas mitoKCa channel is activated by protein kinase A (PKA). However, phosphatidylinositol 3-kinase (PI3-K) is linked to neither mitoKATP nor mitoKCa channels. We have demonstrated that bioactive substances modulate the opening of mitoKATP channels via a PKC-dependent pathway or opening of mitoKCa channels via a PKA-dependent pathway and thereby protecting the heart from ischemia/reperfusion injury. Several endogenous substances such as adenosine and bradykinin can reduce infarct size by activation of mitoKATP channels in a PKC-dependent manner. Adrenomedullin, a potent vasodilator peptide, potentiates the opening of mitoKCa channels by PKA activation. Treatment with adrenomedullin prior to ischemia results in the reduction of infarct size via a PKA-mediated activation of mitoKCa channels. Thus, some endogenous substances confer cardioprotection via PKA- or PKC-mediated activation of mitoKATP or mitoKCa channels. Keywords:: cardioprotection, mitochondrial ATP-sensitive K+ channel, mitochondrial Ca2+-activated K+ channel, protein kinase A, protein kinase C, cardiac disease